Recurrent desmoid tumors with ureteric fistula: a case report and literature review - Yu, LongDi; Yuan, Chi; Wang, Kai; Li, JiaJie; Ma, Xue (Frontiers in Pediatrics, 2025)
BackgroundDesmoid tumors (DT) is a rare soft tissue tumor classified as a borderline neoplasm. It exhibits locally aggressive growth and is prone to postoperative recurrence.Case presentationWe reported the first case of adolescent pelvic DT ureteral fistula, and report the patient's all progress of diagnosis and treatment. A recurrent pelvic DT in an adolescent female patient who initially underwent surgical resection but experienced recurrence, was effectively treated with sorafenib. Later, however, the patient's tumor changed from solid to cystic solid mixed, increasing in size, and the patient developed right hydronephrosis and hydroureter. Patients who underwent right sided antegrade pyelography were diagnosed with right sided ureteral desmoid tumor fistula and urinary fistula-related pseudocysts. Following treatment with right sided percutaneous nephrostomy, their condition improved, with resolution of right sided hydronephrosis and hydroureter, as well as partial shrinkage of the cystic component.ConclusionDT can rarely result in the development of DT-ureteral fistulas. For patients with DT responsive to medical therapy, physicians should closely monitor tumor progression and pay attention to its invasion of adjacent organs and potential complications. Physicians need to balance therapeutic efficacy and quality of life when making treatment strategies for young patients.